KEMAMPUAN MEMENUHI KEWAJIBAN DAN RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2018 - Hendrianto; Gevin Raymond Sihombing (Program Studi Magister Manajemen Universitas Advent Indonesia, 2021)
Every investor always requires a high stock return in order to gain profits in investing. This study aims to find answers to the effect of the ability to fulfill obligations against stock returns with profitability as a variable mediator. The sample of this research is in the form of financial statements for 2015-2018 on banking companies that listed on LQ 45 Indonesia Stock Exchange. The conclusions of this study indicate that only the effect of profitability against stock returns and the effect of ability to fulfill obligations on profitability has a significant effect, while the other hypotheses have no effect.